Religiosity and Fundamentalism as Factors of Perception of Gender Equality - Baroroh, Umul (Sawwa: Jurnal Studi Gender, 2024)
As a non-religious public university, Diponegoro University accommodates students from various religious and fundamentalist backgrounds. Since a person's religious values have an influence on their perspective on the values of inter-sex relationships, it is suspected that both variables also influence their perspective on these relationships. The purpose of this study is to examine the effects of religiosity and religious fundamentalism on the perception of gender equality among Muslim students in Indonesia. Based on the literature review, it is hypothesized that religiosity and religious fundamentalism have a negative impact on the perception of gender equality. The study employs a quantitative approach with a survey design. Data were collected using a questionnaire specifically designed for Muslim students. The study involved 294 Muslim students from Diponegoro University, Semarang, Indonesia. The participants were selected using a cluster sampling technique based on faculty, study program, and class. Hypothesis testing was conducted using multiple regression analysis. The findings reveal that Muslim students’ perception of gender equality is negatively influenced by religiosity and religious fundamentalism. However their total contribution to the perrception is small, 6.4% for males and 5.6% for females. Further research is needed to explore this relationship in greater depth.